Pelatihan Kewirausahaan Pembuatan Bakso Ikan Dan Perhitungan Laba Usaha Bagi Mahasiswa Ilmu Ekonomi Uncen - Sarlota Arrang Ratang; Mesak Iek (The Community Engagement Journal, 2019)
The objectives of the activity are: students Make a visit to the location of partner making fish meatballs, students Hold a practice on how to make hygienic fish meatballs, students Hold a practice on how to record financially in a simple manner (perhitunagn business profits) so that they are able to manage financial business well. is the demonstration method that is carried out is divided into two types, namely demonstration of methods and demonstration of results. Demonstration method is a training technique in the form of activities to show in real terms how to apply the technology of making fish meatballs that have proven to be beneficial for the use of fish and / or business. This entrepreneurship training activity can be carried out well and run smoothly in accordance with the planned activities even though not all participants of the activity are able to master the material conveyed due to limited time and this activity is only at the socialization stage or introduction to how to practice meatballs from fish and make a report on operating income. This activity was welcomed very well as evidenced by the active participation of students in this activity starting from the beginning of the activity until finally the activity never left the place of activity.